Service Users' Perspectives on Communicating Compassion in Mental Health Practice - Ellie Wildbore; Carmel Bond; Stephen Timmons; Ada Hui; Shane Sinclair (Wiley, 2024)
ABSTRACTWhen people talk about their healthcare experience, compassion is often a common ingredient in the stories they share. After a decade of healthcare reforms and research on compassion, the experience of receiving compassionate care has been shown to be important to patients and their families. Yet, there is little guidance to inform compassionate practice in the context of providing mental health care. In this article, the authors suggest three things that mental health nurses can use in their practice to demonstrate compassion.